Effect of hydroxytyrosol methyl carbonate on the thermal, migration and antioxidant properties of PVA‐based films for active food packaging. Issue 8 (26th February 2016) - Fortunati, Elena; Luzi, Francesca; Dugo, Laura; Fanali, Chiara; Tripodo, Giusy; Santi, Luca; Kenny, José M; Torre, Luigi; Bernini, Roberta
Abstract : Novel poly(vinyl alcohol) (PVA)/hydroxytyrosolmethyl carbonate (HTyr‐MC) binary films were developed and thoroughly investigated in view of their potential application as active food packaging materials. Abstract: Hydroxytyrosol methyl carbonate (HTyr‐MC), a synthetic non‐cytotoxic hydroxytyrosol‐derived compound showing excellent antioxidant capacity, was obtained in high yield and purity by an ecofriendly procedure and used as active ingredient for poly(vinyl alcohol) (PVA) matrix. Novel PVA/HTyr‐MC binary films were developed by solvent casting in water adding 2%, 5% and 10% by weight of HTyr‐MC to PVA. Morphological, thermal and optical properties, water absorption capacity, migration to food simulant and antioxidant characteristics of PVA/HTyr‐MC films were finely investigated in view of their potential application as active food packaging materials. The morphological and transparency studies underlined that HTyr‐MC was homogeneously dispersed in the PVA matrix and it is able to act as a nucleation agent, influencing the diffusion processes of the water through the polymer chain without negatively affecting the release of the active ingredient. The overall migration levels for all studied formulations were lower than the migration limits permitted by the current legislation for food contact materials while the data of antioxidant assays demonstrated a good antioxidant activity induced by HTyr‐MC presence also at the lowest concentration. These novel films represent a valid and sustainable alternative to non‐ecofriendly‐based materials. © 2016 Society of Chemical Industry